Building Sustainable Tourism: The Adaptation of Digital Transformation on Travel Agencys and Impact on Economic Growth - Margatan, Kevin (Dinasti Publisher, 2025)
The research discusses the role of digital transformation in building sustainable tourism and its relationship to achieving sustainable development goal (SDG) number 8 in Indonesia. Research focuses on digital transformation such as e-commerce, digital marketing, and big data which can improve travel agent businesses and create more opportunities to market tourist destinations. By using the Systematic Literature Review (SLR) method, this research emphasizes that the use of technology in the tourism business has the potential to increase efficiency, reduce operational costs, and enable the provision of services tailored to client needs. However, there are still gaps in research regarding the role of technology in supporting sustainable tourism, especially local community-based and environmentally friendly tourism. The Sustainable Tourism Digital Hub was proposed with the hope of supporting the economic growth of local communities and increasing the inclusiveness and sustainability of the tourism industry, which is in line with SDG 8.